2011
DOI: 10.4317/medoral.17234
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological effects of an antiseptic mouthrinse in irradiated cancer patients

Abstract: Objective: To assess the microbiological effects of an antiseptic, non-alcohol based mouth-rinse containing chlorhexidine and cetylpyridinium chloride, in patients undergoing radiation therapy for head-and-neck cancer. Study Design: This was a parallel, double-blind, prospective, randomized clinical trial, including patients irradiated as part of the therapy of head-and-neck cancer, aged 18-75, with at least 10 teeth, and willing to sign an informed consent. Cancer patients were randomly assigned to one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Associating yourself positively using PerioAid Tratamiento® antiseptic mouthrinse combined with 0,12% of chlorhexidine and 0,05% of cetylpyridinium chloride, in the reduction of Candida spp. colonies in the oral mucosa and tongue, as well as in samples of subgingival periodontal pathogens (P. gingivalis e E. corrodens) during the RT (15) according to the protocol suggested in table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Associating yourself positively using PerioAid Tratamiento® antiseptic mouthrinse combined with 0,12% of chlorhexidine and 0,05% of cetylpyridinium chloride, in the reduction of Candida spp. colonies in the oral mucosa and tongue, as well as in samples of subgingival periodontal pathogens (P. gingivalis e E. corrodens) during the RT (15) according to the protocol suggested in table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of homogeneity or heterogeneity of the studies was evaluated by statistical test Chi-square (χ2) resulting in the acceptance of the null hypothesis (H0) in both tests, due the value of P = 0.8985 (homogeneity) and P = 0,5299 (heterogeneity) be ≥ to decision level α=0.01 and α=0.05, respectively. The H0 of both tests applied to studies of this review confirm that the samples are heterogeneous, in this case, is indicated by the data analysis Random Effects Model of DerSimonian-Laird (12) for evaluation of the following Odds Ratio tests (OR) together with the Relative Risk (RR) to quantify the association between the presence of OMP and the effectiveness of managements of EG and CG with confidence interval of 95% (CI 95%) and decision value of OR ( P < 0.05) and RR ( P < 0.01) for statistical significance (13-15). …”
Section: Methodsmentioning
confidence: 99%
“…Topical, oral and parenteral anti microbials before and during cancer chemotherapy should alter the quantitative and qualitative oral micro flora profile (18). For this reason, the use of anti microbial agents was an exclusion criterion for our study.…”
Section: Discussionmentioning
confidence: 99%
“…The oral cavity is comprised of various boundary surfaces such as the gingiva, buccal mucosa, tongue dorsum, lateral side of the tongue, and hard and soft plate, which are all colonized with a diverse microbiota (Aas et al, 2005). Thus, P. gingivalis can continually interact with OSCC cells in these sites, and this pathogen has been shown to occur frequently in the mouth of oral cancer patients (Mager et al, 2005;Lanzós et al, 2011). Furthermore, antigens of P. gingivalis have also been detected in gingival squamous carcinoma tumours (Katz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%